Proceedings of the 17th ACM Conference on Computer Supported Cooperative Work &Amp; Social Computing 2014
DOI: 10.1145/2531602.2531694
|View full text |Cite
|
Sign up to set email alerts
|

Beyond end user content to collaborative knowledge mapping

Abstract: Most studies of social tools examine usage of each tool in isolation. Instead, we explore how online communities (a) combine multiple social tools, and (b) use social tools together with external tools. Based on interviews with community leaders and quantitative analysis of 128 online community spaces, we explored the combined use of six social software tools-wikis, blogs, forums, social bookmarks, social file repositories, and task-management tools. We contribute a detailed characterization of how enterprise … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 23 publications
0
16
0
1
Order By: Relevance
“…Matthews et al (2014) captured the source of each curated item in an organizational environment and found that both internal and external resources are curated with respect to different tools (wiki, blog, etc.) [12].…”
Section: Curation In Githubmentioning
confidence: 99%
See 2 more Smart Citations
“…Matthews et al (2014) captured the source of each curated item in an organizational environment and found that both internal and external resources are curated with respect to different tools (wiki, blog, etc.) [12].…”
Section: Curation In Githubmentioning
confidence: 99%
“…Matthews et al (2014) captured the source of each curated item in an organizational environment and found that both internal and external resources are curated with respect to different tools (wiki, blog, etc.) [12]. The curation efforts in intranet communities are often performed by community leaders, while members of the communities are encouraged to curate external resources [12].…”
Section: Curation In Githubmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhong et al (2013) conduct surveys of Pinterest and Last.fm users and find that the majority users engage with the curation site for personal interests rather than social reasons (Zhong et al, 2013). A recent study examines the ways that communities leverage a variety of social tools for curation to support vital community activities in a large enterprise environment (Matthews et al, 2014). The authors also call for future studies on curation in public Internet communities (Matthews et al, 2014).…”
Section: Motivations To Curate In the Social Media Eramentioning
confidence: 99%
“…A recent study examines the ways that communities leverage a variety of social tools for curation to support vital community activities in a large enterprise environment (Matthews et al, 2014). The authors also call for future studies on curation in public Internet communities (Matthews et al, 2014).…”
Section: Motivations To Curate In the Social Media Eramentioning
confidence: 99%